Determination of Temazepam Levels in Urine by Gas Chromatography – Mass Spectrometry - Sulistiyo, Joko (Asian Journal of Pharmaceutical Research and Development, 2023)
Temazepam is a benzodiazepine drug belonging to a class IV psychotropic. Temazepam provides a sedative-hypnotic effect that can help with insomnia. Thanks to the sedative-hypnotic effect it produces, many people take this drug to treat various sleep problems. However, if misused for a long period of time this drug can cause dependence. Therefore, to determine the level of temazepam in a person’s body, a confirmation test of temazepam in the urine is needed. The test uses the gas chromatography - mass spectrometry method, this method is the most widely used method in drug testing with very specific results, so the results are not in doubt. This test begins with sample preparation by taking the extract using the solid phase extraction (SPE) method followed by enzyme hydrolysis, centrifugation and derivatization. Based on the tests carried out, positive results were obtained for temazepam with levels of 4444.9895 ng/mL.